2024
DOI: 10.1021/acs.jpclett.3c03625
|View full text |Cite
|
Sign up to set email alerts
|

Self-Trapped Exciton Emission Enhancement in 3D Cationic Lead Halide Hybrids Via Phase Transition Engineering

Xuening Sun,
Min Wu,
Yue Wang
et al.

Abstract: Three-dimensional (3D) cationic lead halide hybrids constructed by organic ions and inorganic networks via coordination bonds are a promising material for solid-state lighting due to their exceptional environmental stability and broad-spectrum emission. Nevertheless, their fluorescence properties are hindered by the limited lattice distortion from extensive connectivity within the inorganic network. Here, a dramatic 100-fold enhancement of self-trapped exciton (STE) emission is achieved in 3D hybrid material [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…To enhance the application prospects of MA 3 Sb 2 I 9 , it is necessary to optimize its band gap and explore the relationship between structure and electrical properties. High-pressure techniques offer a clean and powerful approach to altering the crystal structure and electronic landscape of materials, , thereby enabling adjustments to their physical properties while preserving their chemical composition. Previous studies have demonstrated that pressure can modulate the degree of orbital coupling between atoms by altering the interatomic distance, resulting in optimization of the optical properties and regulation of ion transport processes. Accordingly, it is expected to optimize the band gap and electric transport behavior of MA 3 Sb 2 I 9 through pressure engineering. …”
Section: Introductionmentioning
confidence: 99%
“…To enhance the application prospects of MA 3 Sb 2 I 9 , it is necessary to optimize its band gap and explore the relationship between structure and electrical properties. High-pressure techniques offer a clean and powerful approach to altering the crystal structure and electronic landscape of materials, , thereby enabling adjustments to their physical properties while preserving their chemical composition. Previous studies have demonstrated that pressure can modulate the degree of orbital coupling between atoms by altering the interatomic distance, resulting in optimization of the optical properties and regulation of ion transport processes. Accordingly, it is expected to optimize the band gap and electric transport behavior of MA 3 Sb 2 I 9 through pressure engineering. …”
Section: Introductionmentioning
confidence: 99%
“…As the pressure increases, the average lifetime decreases to 0.32 ns at 3.66 GPa. This reduction is attributed to the suppression of energy transfer processes and a decrease in the number of nonradiative transitions, which lead to an increased number of radiative transitions, shorter lifetimes, and enhanced luminescence. ,,,, After 3.98 GPa, an overlap between free exciton and STE emission is observed in the PL spectra, significantly affecting the average lifetime of the n = 1 phase (Figure b and Figure S9). Figure e shows that the average lifetime of the n = ∞ phase slightly increases from ambient conditions to 1 GPa, followed by a substantial increase from 1 to 1.5 GPa.…”
mentioning
confidence: 99%